Structural racism and the education gradient for early all-cause mortality - Suzanne Bartle-Haring; Riley Whiting (Elsevier, 2022)
There are clear connections between education achieved and health over the course of a lifetime, with higher education achievement being associated with better health. However, the association between education and mortality have differed by race, with minoritized populations reaping fewer benefits from education attained. This paper aims to understand the moderating effect of structural racism (measured at the state level) on the association between education and all-cause early mortality for Black and White participants. We utilize a nationally representative longitudinal sample of youth (NLSY97), and estimates of structural racism for each state through measures of political participation, employment and job status, education attainment ratios, and judicial treatment. Random effects models were then utilized to compare associations between Black and White participants, and assess the association of education on early mortality. Results indicate significant, yet nuanced findings in each of the models assessed suggesting that Black and White participants experienced diminished returns of education on the probability of early mortality. Findings support previous research suggesting that structural racism is costing all citizens, but is especially harmful for minoritized populations.